A Triticum vulgare Extract Exhibits Regenerating Activity During the Wound Healing Process - Tito A; Minale M; Riccio S; Grieco F; Colucci MG; Apone F (Dove Medical Press, 2020)
Annalisa Tito, 1 Massimiliano Minale, 2 Salvatore Riccio, 2 Fabrizia Grieco, 2 Maria Gabriella Colucci, 1, 3 Fabio Apone 1, 3 1Arterra Bioscience Srl, Naples, 80142, Italy; 2Farmaceutici Damor S.p.A., Naples 80145, Italy; 3VitaLab Srl, Naples, 80142, ItalyCorrespondence: Annalisa TitoArterra Bioscience Srl, via Benedetto Brin 69, Naples 80142, ItalyTel +39 0816584411Fax +39 081 2144864Email annalisa@arterrabio.itIntroduction: Chronic skin lesions represent a problem of increasing occurrence, mostly due to the global ageing of the world population. Research in skin care and dermatology is constantly looking for new non-invasive solutions, preferably those based on the use of natural certified products, able to accelerate the spontaneous skin repair mechanisms and without altering the skin normal appearance and functionality. The wound healing process in the skin is finely regulated by several factors and orchestrated mechanisms, which modulate the progression and the fitting of different consequent phases, including haemostasis, inflammation, cell proliferation and tissue remodelling. It was previously shown that a patented Triticum vulgare aqueous extract was able to trigger the skin repair process by stimulating new tissue growth and reducing the expression levels of inflammatory mediators, such as IL-6, TNFα, prostaglandin E2, and nitric oxide.Methods: Scratch assay was performed in Human Dermal Fibroblasts (HDF). The production of fibronectin was measured by gene expression, protein quantification and localization using specific antibodies in HDF. The polymerization of actin was measured using rhodamin-phalloidin in HDF. The epidermal lipid content was estimated in HaCaT (human spontaneously immortalized keratinocytes) using Nile Red staining and the increasing GBA gene expression and activity was demonstrated by RT-PCR and enzymatic activity assay.Results: In the present study, it was demonstrated that the T. vulgare extract enhanced cell migration inducing the synthesis of fibronectin, new actin polymerization and stimulating the expression of the Hyaluronan Synthase 2. Furthermore it improved the restoration of the epidermal barrier stimulating lipid synthesis.Conclusion: In conclusion, we demonstrated that the T. vulgare extract possessed promising potential to be developed as a wound healing promoting agent in skin care and dermatology.Keywords: plant extract, wound healing, skin cell culture, ECM component, epidermal barrier